SDGs Achievement on Social Pillars: A Spatiotemporal Analysis of Education Participation in Indonesia for the 2015 to 2021 Period - Dian Rizqi Khusnul Khotimah (Jurnal Educative: Journal of Educational Studies, 2022)
Since 2015, education has become an important part of social pillars supporting Sustainable Development Goals (SDGs). The fourth goal of SDGs, quality education, emphasizes inclusive, equitable, and lifelong education. The Indonesian government has prioritized region-based sustainable development in its 2020-2024 Medium-Term National Development Plan (RPJMN). It has also emphasized the achievement of secondary and higher education levels in Human Resource (HR) development targets. This achievement can be realized if there is equal distribution of educational participation, starting from the primary to the tertiary level. This quantitative study aims to analyze and elaborate spatiotemporal insights at every level of education regarding the development of educational participation in Indonesia during the period of 2015 to 2021. Results have shown that there was a significant spatiotemporal development in the achievement of inter-level educational participation during this period. The implementation of regional-based education development needs to be optimized to achieve an inclusive distribution of educational participation among provinces.Sejak 2015, pendidikan menjadi salah satu bagian penting dalam pembangunan berkelanjutan (SDGs) pilar sosial. Tujuan ke-4 SDGs yaitu pendidikan berkualitas, penitikberatan pada pendidikan inklusif, merata, dan sepanjang hayat. Pemerintah Indonesia menekankan pembangunan berkelanjutan berbasis wilayah pada RPJMN 2020-2024. Pemerintah juga menekankan capaian jenjang pendidikan menengah ke atas pada highlight sasaran pembangunan SDM. Capaian tersebut dapat terwujud apabila terdapat pemerataan partisipasi pendidikan secara terstruktur dan berkesinambungan, mulai dari jenjang pendidikan SD hingga Perguruan Tinggi. Tujuan dari penelitian ini adalah menganalisis dan mengelaborasi insight secara spasiotemporal pada setiap jenjang pendidikan mengenai perkembangan capaian pembangunan dan pemerataan partisipasi pendidikan di Indonesia pada periode 2015 hingga 2021. Hasil penelitian menunjukkan bahwa terdapat perkembangan signifikan pada pola capaian partisipasi pendidikan antarjenjang dari periode 2015 hingga 2021. Pengimplementasian pembangunan pendidikan berbasis wilayah perlu dioptimalkan untuk mewujudkan pemerataan karakteristik partisipasi pendidikan antarprovinsi